Navigating the aid world: barriers to the effective participation of local NGOs in the post-conflict environment of Timor-Leste - Butler, Lynne Margaret (Curtin University, 2008)
This thesis presents an ethnographic study of a small local non-government organisation (NGO) negotiating its way through the complex, multi-layered, postconflict, post-emergency environment of Timor-Leste. This is an environment that remains dominated by the aid industry, an industry that initially came to restore order and provide humanitarian support in the violent aftermath of the 1999 independence vote and stayed on to build a new Timor, in many ways created in its own image. In this environment a small local NGO struggled to maintain not only its vision and mission, but to fit within a new set of externally imposed conditions and regulations in order to serve its communities' needs.Using ethnographic data gathered in the field over eleven months, this study paints a picture of a post-emergency environment on the ground and in the daily life of a local NGO within that environment. Combining ethnographic and interview data from local and international aid and development practitioners, the study also identifies the internal and external challenges faced by the local NGO in navigating its way through this environment. The internal challenges faced are largely in response to externally imposed conditions, and include the adaptation to new language and communication technologies, new styles of leadership and organisation management, new financial accountability processes and procedures. All of these challenges are coupled with the lack of experienced and skilled staff. The external issues relate to interactions and relationships the local NGO has with the aid industry, and the issues arising out of these engagements including ideological differences, donor dependency, unequal relations, and externally imposed directives.While acknowledging that these are very real challenges, this thesis argues that it is the underlying factors behind the presenting challenges that are the real barriers to the effective participation of a local NGO in the post-conflict, post-emergency environment. Using post-development writings and Foucauldian theories as a theoretical framework, this thesis explores how thought, ideology and action are governed and controlled by the subtle mechanisms of liberal governance, (particularly in their redefinition), and local language is appropriated and reconceptualised as a tool of governance. It is the inability to understand or detect these subtle mechanisms of governance that often limits the degree to which an NGO can be said to act self-determinedly, or in full awareness of the situation, as they navigate a path through this foreign and often baffling post-emergency environment.This research adds to the emerging academic body of research on NGOs in postconflict, post-emergency environments. On a practical level it provides aid and development organisations and aid practitioners with a detailed 'insider's' view of the operations of a local NGO and the impacts on a small organisation of externally imposed conditions, regulations and hidden agendas. Finally, it provides field workers intending to conduct research in post-conflict, post-emergency environments with an introduction to the issues and problems associated with this type of research.